Experience of Dexmedetomidine using for intraoperative analgosedation during ophthalmic operations - Maxim Khodakovsky (Interdisciplinary Academy of Pain Medicine, 2021)
Background. The aim of the study is to evaluate the quality and safety of the sedative effect of anesthesia in ambulant ophthalmic surgery by using continuous intravenous infusion of Dexmedetomidine. Materials and Methods. Patients were randomized into groups by age (people from 65 to 75 years old, old age 76 years, middle age, young people, children), by gender (men, women). The physical status of patients was assessed using the ASA scale and the dynamics of vegetatic activity by the Kerdo index. Sedation was assessed using the Richmond Sedation Scale RASS. Results. It was found that the difference in the frequency of adverse effects of the appointment of Dexmedetomidine clearly confirms the need to adjust the dose of Dexmedetomidine, depending on the state of the autonomic nervous system. The use of Dexmedetomidine according to the recommendations made it possible to achieve a safe level of sedation and eliminate side effects in ambulant ophthalmic surgery. Conclusions: